Evaluating pluricultural and pluricultural awareness of pre-primary educators by means of language portraits - Rokita-Jaśkow, Joanna; Król-Gierat, Werona (Glottodidactica, 2024)
Developing plurilingual and intercultural awareness is an essential aspect of Early Childhood Education and Care (ECEC) teacher training programmes in countries like Poland, with its population becoming more diverse linguistically. Plurilingual and pluricultural awareness can aid teachers in teaching early foreign languages efficiently and in working with children from diverse linguistic and cultural backgrounds. To achieve this goal, language portraits have been recognised as a useful tool in transformative and multilingual pedagogy (Coffey 2015; Hopp et.al. 2020; Lau 2016) as they help educators become more aware of their linguistic repertoires and how they can use them when working with young learners (Prasad 2020; Soares et al. 2021). This study analyses language repertoires of 75 pre-primary educators utilising the techniques of language portrait presented in the PEPELINO portfolio (Goullier et al. 2015). The content analysis of data indicates a vast repertoire of languages present in the teachers’ lives; however, they are significant only in the emotional dimension and less in the cognitive and communicative ones. This finding is interpreted as a result of a solid monolingual ideology rooted in the teachers, lack of plurilingual and pluricultural awareness and thus foreseeing difficulties in teaching a foreign language or in linguistically diverse classes. Guidelines for ECEC teacher education are provided.